(untitled) (Boletin Médico de Postgrado, 2020)
In order to evaluate the efficacy of magnesium sulphate as a coadjuvant in postoperative analgesia in patients undergoing open cholecystectomy admitted to the Hospital Central Universitario Dr. Antonio Maria Pineda during the May - August 2018 period, we performed a controlled single blind study with a sample of 50 patients randomly assigned to two groups (1:1 ratio): experimental group which received 50 mg/kg intravenous magnesium sulfate plus ketoprofen 100 mg IV and control group which only received ketoprofen 100 mg IV. The intensity of pain was estimated through the visual analogue scale (VAS). Basal pain intensity was less in the experimental group. Analgesic rescue doses were higher in the control group (p < 0.05) while nausea was only seen in this group. 62.5% of patients of the control group with VAS > 4 required rescue medication between 30 minutes and 12 hours post-surgery while 37.5% of patients of the experimental group received rescue medication between 8 to 24 hours post-surgery (p < 0.05). The results show that magnesium sulphate is an effective alternative in the treatment of postoperative pain.